A rare case of isolated preperitoneal necrotizing myofasciitis: a diagnostic dilemma in the absence of cutaneous signs - Solanki, Ashvi U.; Jain, Madhuri M.; Iyer, Sandhya P. (International Surgery Journal, 2025)
Surgical infections are a diverse group of conditions including intra-abdominal infections, necrotizing soft tissue infections (NSTI’s), and abscesses, contributing significantly to global morbidity and mortality, often necessitating surgical or procedural intervention for cure. Isolated extraperitoneal and retroperitoneal NSTI’s are uncommon. We present a rare case of an adult male in mid-thirties with isolated anterior infraumbilical preperitoneal necrotizing myofasciitis, in the absence of any known etiological factors for NSTI’s. Patient presented with severe abdominal pain of 1 day duration, with no complaints of urinary symptoms, vomiting, constipation or obstipation. Laboratory investigations showed metabolic acidosis with leukocytosis. Radiological investigations including abdominal X-ray and plain abdomen & pelvic CT (computed tomography) showed air foci in the extraperitoneal space with no evidence pneumoperitoneum. Radical debridement was done via exploratory laparotomy; intraoperatively necrotic tissue was present in extraperitoneal space with no evidence of injury to hollow viscus or urinary bladder. Post operatively patient was managed in intensive care unit (ICU), received HBO (hyperbaric oxygen) therapy and was followed up on outpatient basis.